Nursing Leadership in a Rapidly Aging Society: Implications of "The Future of Nursing" Report in Japan. (27th June 2012) - Masaki, Harue; Nagae, Hiroko; Teshima, Megumi; Izumi, Shigeko
Abstract : The recent US Institute of Medicine (IOM) report about the future of nursing highlights the areas where nurses can serve, contribute, and move forward to improve health care in the United States. Japanese nursing scholars examined the IOM report for its implications in the Japanese context and explored the future of nursing in Japan. The purpose of this paper is to provide support for the premise that the report's recommendations could have implications for the future of nursing outside of the United States, especially in Japan. Particular areas and activities by nurses in Japan will be presented as examples of nurses taking leadership in designing care for the rapidly aging society of Japan.